Changes in the Antioxidant and Mineral Status of Rabbits After Administration of Dietary Zinc and/or Thyme Extract - Kucková, Katarína; Grešáková, L'ubomíra; Takácsová, Margaréta; Kandričáková, Anna; Chrastinová, L'ubica; Polačiková, Mária; Cieslak, Adam; Ślusarczyk, Sylwester; Čobanová, Klaudia (Frontiers in Veterinary Science, 2021)
This study was aimed at determining the impact of organic zinc (Zn) and thyme extract (TE) administration, given alone or together for 6 weeks, on the antioxidant and mineral status (Zn, Cu, Fe, Mn) in the plasma and tissues of growing rabbits. A total of 96 rabbits of age 35 days were randomly assigned to 1 of 4 treatment groups: a control group (C), a Zn group supplemented with dietary zinc (50 mg/kg), a TE group receiving thyme extract applied in drinking water (1 ml/L), and a Zn + TE group treated with both additives. Lipid peroxidation in the plasma was influenced by Zn intake and in the kidney was affected by both the Zn and TE treatment (P < 0.05). Zn supplementation led to a significant increase in glutathione peroxidase activity (P = 0.017), total antioxidant capacity (P = 0.009) and total thiol groups level (P = 0.047) in the kidney, with the highest values occurring in rabbits receiving the combination Zn + TE. Administration of TE influenced Zn content in the kidney (P < 0.001), while zinc intake decreased Cu concentration in muscle (P = 0.021). In conclusion, the simultaneous administration of organic Zn and TE positively affected the antioxidant response of kidneys and can be used for improving the antioxidant status of growing rabbits.